DELINEATION OF POTENTIAL MINERAL ZONES USING INTEGRATED AEROMAGNETIC AND AEROGRAVITY DATA OVER PART OF ZAMFARA STATE, NORTH WESTERN NIGERIA - Sani, Ibrahim; Shehu, Jamaluddeen S.; Ahmed, Faiza (FUDMA JOURNAL OF SCIENCES, 2025)
This study aims to delineate potential mineral-bearing zones in Zamfara State using integrated aeromagnetic and aerogravity data interpretation. Acquired aeromagnetic and aerogravity data of part of Zamfara State that lies between latitudes 11°30′0″N and 12°30′0″N, and longitudes 6°00′0″E and 7°00′0″E were used to delineate structures that may host minerals in the study area. The area forms part of the northern Nigerian basement complex with granite, migmatite, biotite, gneiss, diorite, medium course grained, and migmatite augen gniess as host rocks in the region. Advanced filtering techniques—FVD, AS, and SPI—were applied to enhance structural features, estimate source depths, and identify lineaments indicative of mineralization. The data were subjected to various filtering techniques such as first vertical derivative (FVD), analytical signal (AS), source parameter imaging (SPI) and lineaments analysis. The FVD maps for both the data enhance shallow anomalies ranges from -170nT/m to 0.166nT/m and -66.8mgal/m to 74.4mgal/m. The AS maps indicate magnetic anomaly edges and their source positions with values 0.088nT/m to 0.4417nT/m and 6.5mgal/m to 118.4mgal/m. Anomalies indicating possible mineral zones were observed at depths ranging from approximately 35 m to over 5,000 m. SPI maps revealed the depth to the anomalous sources ranges from 35.0m to 357.0m and 260.8m to 5192.5m. Lineaments analysis determined faults and fractures of the rocks within the study area. The integrated analysis delineated several structurally controlled zones near Lugga, Maru, Yantauri, and Tudun Wada with strong geophysical signatures consistent with mineralization. "The isolated the potential mineral zones are 12.450N to 12.060 N and...